Temporal Change and Fishing Down Food Webs in Small-Scale Fisheries in Morondava, Madagascar - Gough, Charlotte; Ateweberhan, Mebrahtu; Godley, Brendan J.; Harris, Alasdair; Le Manach, Frédéric; Zafindranosy, Erude; Broderick, Annette C. (Frontiers in Marine Science, 2022)
Small-scale fisheries (SSFs) are often undervalued and unmanaged as a result of a lack of data. A study of SSFs in Menabe, western Madagascar in 1991 found diverse catches and a productive fishery with some evidence of declining catches. Here we compare data collected at the same landing site in 1991 and 2011. 2011 had seven times greater total monthly landings due to more people fishing and higher individual catches. Catch composition showed a lower mean trophic level in 2011 indicating overfishing, the true extent of which may be masked due to changes in technology and fishing behaviours. Limited management action since 2011 means these trends have likely continued and an urgent need for both greater understanding, and management of these fisheries remains if they are to continue providing food and income for fishing communities.